Simulation of induction machine on a personel computer using turbo C++ / Aziman Abdullah - Abdullah, Aziman (1995)
This project is concerned on the improvement of a computer simulation software that could be used to simulate the dynamic performance characteristics of various ratings of induction motor complete with graphical analysis display to be operated on a personal computer and can be used for educational purposes. The machine analysis uses the well known Park's form of linear equations that has been transformed into state vector matrices. The equations are solved using a number of numerical methods for purposes of studying the performance of the mathematical techniques as applied in this simulation.